TINJAUAN KRIMINOLOGIS TERHADAP PELAKU PENGANGKUTAN KAYU TANPA IZIN DI KAWASAN HUTAN PRODUKSI MUTIS TIMAU RTK 183 BIPOLO KABUPATEN KUPANG - Aryanto Huru; Jimmy Pello; Heryanto Amalo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines a criminological review of perpetrators involved in the unauthorized transportation of timber within the Mutis Timau Production Forest Area RTK 183 Bipolo, Kupang Regency, as reflected in the Decision of the Oelamasi District Court Number 37/Pid.Sus-LH/2025/PN Olm. The research questions addressed in this study are: (1) What are the contributing factors behind the occurrence of unauthorized timber transportation in the Bipolo Area, Kupang Regency? (2) How are rehabilitation and guidance efforts carried out toward perpetrators of unauthorized timber transportation in the Bipolo Area, Kupang Regency? This study employed an empirical research method with a descriptive qualitative approach. The research was conducted at The Class IIB Detention Center of Kupang, the Regional Office for Natural Resources Conservation (KSDA) of East Nusa Tenggara, the Regional Technical Implementation Unit (UPTD) of the Forest Management Unit (KPH) for Kupang Regency, Kupang City, and Sabu Raijua, and the Head of the Forest Protection and Forestry Law Enforcement Agency for the Java–Bali–Nusa Tenggara Region, c.q. Section III Manggarai Barat, Kupang Gakkum Post. The findings of this study indicate that: (1) The contributing factors behind unauthorized timber transportation in the Bipolo Forest Area include internal factors, namely economic need, low levels of education and understanding of forestry law, and self-rationalization by the perpetrators; and external factors, namely weak forest area supervision due to limited human resources and infrastructure, high market demand for timber, social environmental influences that normalize illegal behavior, and the involvement of intellectual actors who exploit laborers as field operatives. (2) Rehabilitation and guidance efforts toward the perpetrators are carried out not only through a repressive approach via criminal sentencing, but also through rehabilitative and preventive measures, including legal counseling and forestry law education, environmental awareness development, vocational skills training, economic empowerment of communities surrounding the forest area, and strengthened cooperation among BBKSDA, UPTD KPH, Forestry Law Enforcement (Gakkum), local government, and the community through the establishment of Community Forest Police Partnership groups (MMP).